2014
DOI: 10.1021/cb500086e
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals Perturb Membranes and Promiscuously Alter Protein Function

Abstract: A wide variety of phytochemicals are consumed for their perceived health benefits. Many of these phytochemicals have been found to alter numerous cell functions, but the mechanisms underlying their biological activity tend to be poorly understood. Phenolic phytochemicals are particularly promiscuous modifiers of membrane protein function, suggesting that some of their actions may be due to a common, membrane bilayer-mediated mechanism. To test whether bilayer perturbation may underlie this diversity of actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
330
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(346 citation statements)
references
References 84 publications
13
330
3
Order By: Relevance
“…These, their analogues and similar natural products persist in being followed up as drug leads and used as 'positive' controls even though their promiscuous actions are welldocumented 8,9 .…”
Section: All Pain No Gainmentioning
confidence: 99%
“…These, their analogues and similar natural products persist in being followed up as drug leads and used as 'positive' controls even though their promiscuous actions are welldocumented 8,9 .…”
Section: All Pain No Gainmentioning
confidence: 99%
“…2B). Concentrations higher than 10 μM were not attempted because capsaicin and other lipophilic molecules at higher concentrations will nonspecifically alter the activity of ion channels through perturbation of the membrane (21). Sequence logo of the alignment between TRPV1 and TRPV2 channels.…”
Section: Trpv2_quad Is Activated By Resiniferatoxin But Antagonized Bymentioning
confidence: 99%
“…A number of studies have identified curcumin as a membrane-modulating agent, for example, it could alter lipid bilayer properties and influence structurally and functionally unrelated proteins, including a wide range of membrane proteins (Ingolfsson et al, 2007(Ingolfsson et al, , 2014, We have previously reported that cellular membrane lipid raft is crucial in mediating BoHV-1 entry into MDBK cells (Zhu et al, 2010). Here we demonstrated that curcumin affected BoHV-1 entry into MDBK cells.…”
Section: Discussionmentioning
confidence: 53%